Frequency design of LEO-based navigation augmentation signals for dual-band ionospheric-free ambiguity resolution - Ma, Fujian; Zhang, Xiaohong; Hu, Jiahuan; Li, Pan; Pan, Lin; Yu, Siqi; Zhang, Zhiyu (GPS solutions, 2022)
Due to the spectrum congestion of current navigation signals in the L-band, it is difficult to apply for another two proper frequencies in this band for future low earth orbit (LEO)-based navigation augmentation systems. A feasible frequency scheme of using the combined frequencies in the L, S and C bands is proposed. A high-efficiency modulation scheme, termed continuous phase modulation, is adopted to make full use of the very limited spectrums and satisfy the radio frequency compatibility with the existing navigation systems, radio astronomy, and microwave landing systems. The high propagation loss in the S and C bands is absent for LEO, as the power margin owing to the short-distance propagation has compensated the frequency-dependent attenuation. Besides, for high-precision positioning, we consider the specific integer ratios between frequencies and propose a strategy for LEO precise point positioning (PPP) ambiguity resolution (AR) by directly fixing the L + S or L + C dual-band ionospheric-free (IF) ambiguity. Based on the simulated data, the quality of fractional cycle biases (FCBs) and the performance of PPP AR are analyzed. After removing the FCBs, 100.0, 99.7 and 71.7% of the fractional parts are within ± 0.15 cycles for GPS narrow-lane, LEO L + S dual-band IF and LEO L + C dual-band IF float ambiguities. At user stations, the convergence time of GPS PPP in static mode can be significantly shortened from 17.9 to within 2.5 min with the augmentation of 5.44 LEO satellites. Furthermore, compared with ambiguity-float solutions, the positioning accuracy of GPS AR + LEO AR solutions in east, north and up components is improved from 0.008, 0.008 and 0.027 m to 0.002, 0.003 and 0.011 m for 10-min sessions, respectively, and the fixing rate after time to first fix is almost 100%.